Wound Myiasis Caused by Sarcophaga (Liopygia) Argyrostoma (Robineau-Desvoidy) (Diptera: Sarcophagidae): Additional Evidences of the Morphological Identification Dilemma and Molecular Investigation - Annunziata Giangaspero; Marianna Marangi; Antonio Balotta; Claudio Venturelli; Krzysztof Szpila; Antonella Di Palma (The Scientific World Journal)
In Mediterranean countries, Sarcophaga (Liopygia) crassipalpis, Sarcophaga (L.) argyrostoma, and Sarcophaga (L.) cultellata share the same ecological niche and can be responsible of myiasis. In this study, the main morphological characters of a larva found in a hospitalized woman were described and illustrated by light and SEM microscopy and the features discussed. Then, a fragment within the mitochondrial encoded cytochrome c oxidase subunit I (coxI) gene of ~735 bp was amplified and sequenced. The molecular investigation was necessary to confirm the species Sarcophaga (Liopygia) argyrostoma (99% of identity). Our findings showed that morphological descriptions of larvae of three Mediterranean species of Liopygia available in several papers might not be clear enough to allow for comparison and correct identification. Until results of reliable comparative studies of larvae of all three species will be available, the use of molecular tools is crucial, to avoid misleading or incomplete identification, and in particular when a myiasis becomes a legal issue.